If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + x + 1 = 31 Reorder the terms: -15 + 1 + x = 31 Combine like terms: -15 + 1 = -14 -14 + x = 31 Solving -14 + x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + x = 31 + 14 Combine like terms: -14 + 14 = 0 0 + x = 31 + 14 x = 31 + 14 Combine like terms: 31 + 14 = 45 x = 45 Simplifying x = 45
| -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 | | 8-4x=4-3(2x-6) | | 5(8v-8)=-6 | | 2x+3=-55 | | Y=1/2X-18 | | 65=5(5x-17) | | -2(x-3)=5(2x+13) | | 14+A=2-2A | | 2/3x–17=-9 | | -q=-52 | | f(x)=6xsquar | | (15)65=5(5x-17) | | 1-r=9 | | ln(x-3)=ln(1/x) |